3D scale space for structure analysis of 2D image series - Logeswaran, , R; Eswaran,, C (2005)
Scale space has become a popular biological motivated technique in image processing for analyzing characteristics within images. This technique identifies structures within an image through multi-resolution analysis of the image. Commonly, 3D objects are sampled as a series of 2D images using conventional acquisition techniques. This paper describes the implementation considerations for the scale space analysis of 3D volume data reconstructed from series of 2D images.